(untitled) (Experimental biology, 2023)
SARS - COV2 or COVID-19 caused 2020 the greatest pandemic since the end of WW1 and crippled the global healthcare and economy within a relatively short period of time. This article reveals the vaccination issues by understanding the innate and adaptive immune responses and how tightly they are interconnected with each other. There are also to grasp the cellular and humoral parts of immunity and receptor binding recognition mechanisms, antibody neutralization, and antibody mediation both in adaptive and innate immunity to be discussed. The defense strategies of immunity are the objects along with clinical cases to discuss and how effective or not effective vaccination could be in a view of antibody role in creating immunity against this virus. This article will be interesting to those who are planning to design either monoclonal research or strategies for COVID-19 treatment and even vaccination drug design.